SENSORY METHODS THAT SUPPORT PREDICTIVE MAINTENANCE IN AN IOT OPTICS - Magalhães Viegas Junior, Daniel (Journal of Interdisciplinary Debates, 2024)
The research seeks to build a device that aims to identify properties of hydraulic oil in hydraulic mining excavators. The need to obtain research data allows us to improve the maintenance processes of this equipment, enabling an improvement in the production process and management of the use of tools.